Chapter «Amerai il prossimo come te stesso» - Leão, Isabel Ponce de (Libere carte, 2023)
You will love the next as you love yourself was the motto of life and work of David Sassoli, born communicator, who understanded that thought art we fight for any United and democratic Europe who innovates, protects and enlights. Six plastic artist understood his message and translated into different languages prolonging his plea.